Backyard Poultry Rearing and Adoption of Management Practices in Hassan District of Karnataka - OR, Nataraju; R, Vinaykumar; KH, Nagaraj (Journal of Agricultural Extension Management, 2018)
An attempt was made to analyse the adoption of poultry rearing and management practices by the backyard poultry farmers. The study was conducted in ten villages of Hassan district of Karnataka. The respondents had admirable knowledge about backyard poultry rearing. However, majority of the farmers are maintaining local birds compared to improved back yard poultry birds. The study also revealed that, the incidence of Ranikhet disease was severe when compared to fowl pox. The respondents had very fair knowledge regarding local practices to counteract the diseases. Though the farmers had better knowledge on disease management, the adoption level of practices recommended by the agriculture and veterinary universities was very poor. It is implied that suitable awareness programs should be organized for backyard poultry farmers on vaccination and other scientific methods for effective management of Ranikhet and other diseases.